Neurological and psychiatric symptoms caused by congenital venous anomaly: clinical case and literature review - Gataveckaitė, M.; Burbienė, R.; Mameniškienė, R. (Neurologijos seminarai, 2023)
One of the most common vascular brain malformations is developmental venous anomaly (DVA). This anomaly is usually considered to be asymptomatic but there are some reports in the literature about DVA causing neurological symptoms due to neurovascular compression, obstructive hydrocephalus, venous infarction, or intracerebral hemorrhage. There are no publications on DVA causing psychiatric symptoms. This paper presents a clinical case of DVA in which the patient develops a mood disorder along with neurological symptoms that are typical for a parietal brain lesion. Along with this clinical case, a review of literature is presented which includes classification of vascular brain malformations, prevalence of DVA, clinical manifestations, and characteristics in imaging studies. The article also reviews the functions of the parietal lobe, discusses mood disorders possibly related to parietal lesions, and briefly introduces cyclothymic disorder.